Finanzas e Inversiones Inmobiliarias - AF190 - 202302 - Gómez Sánchez Arbulú, Alvaro Martin (2023)
This course is a study of the major aspects of real estate finance and investment. The course will focus on the perspectives of various stakeholders including corporate, private and public investors. The primary emphasis will be on real estate as an investment, rather than individual home ownership. The course will start with a general introduction to real estate including terminology and the key drivers of the real estate investment decision. From there, the emphasis will shift to building increasingly accurate financial models to assess the expected risk and return of various types of real estate. Extensive use of Excel will be required. Prerequisite Requirements The prerequisites for this course are FIN 311, Introduction to Finance, or FIN 360, Quantitative Financial Management. To better prepare you to successfully take this course, we have provided review materials on Time Value of Money (TVM) in the Table of Contents -> Reference Information area of D2L.